2013
DOI: 10.1142/s0219061313500037
|View full text |Cite
|
Sign up to set email alerts
|

Proof Theory of Weak Compactness

Abstract: We show that the existence of a weakly compact cardinal over the Zermelo-Fraenkel's set theory ZF is proof-theoretically reducible to iterations of Mostowski collapsings and Mahlo operations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…We need Theorem 1.2 in [6][7][8][9] for proof-theoretic analyses of set theories for weakly compact cardinals, first-order reflecting ordinals, ZF and second-order indescribable cardinals. In these analyses, a provability relation H ⊢ α c Γ derived from operator controlled derivations is defined to be a fixed point of a strictly positive formula.…”
Section: Theorem 12 Fix I (T ) Is a Conservative Extension Of Any Sementioning
confidence: 99%
“…We need Theorem 1.2 in [6][7][8][9] for proof-theoretic analyses of set theories for weakly compact cardinals, first-order reflecting ordinals, ZF and second-order indescribable cardinals. In these analyses, a provability relation H ⊢ α c Γ derived from operator controlled derivations is defined to be a fixed point of a strictly positive formula.…”
Section: Theorem 12 Fix I (T ) Is a Conservative Extension Of Any Sementioning
confidence: 99%
“…Let us announce an extension of Theorem 2.2 in [6,7] to the indescribable cardinals over ZF + (V = L).…”
Section: Proposition 23 For Any Classmentioning
confidence: 99%
“…In [3] we showed that the existence of a weakly compact, i.e., Π 1 1 -indescribable cardinal over the Zermelo-Fraenkel's set theory ZF is proof-theoretically reducible to iterations of Mostowski collapsings and Mahlo operations, while in [4] we describe a proof-theoretic bound on definable countable ordinals in ZF. In this paper we do the same reductions for the existence of a Π 1 N -indescribable cardinal, cf.…”
Section: Introductionmentioning
confidence: 99%